Performance Analysis of the Public Works and Spatial Planning Agency in Infrastructure Development in West Nusa Tenggara, Indonesia - Rifaid, Rifaid; Rachman, M. Taufik; Suhartono, Yudhi (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study evaluates the performance of the Public Works and Spatial Planning Office of West Nusa Tenggara Province in developing the region, specifically in water resources and transportation infrastructure. A qualitative methods approach was utilized in analyzing relevant documents to assess the office's performance. The research reveals that the performance of the office has declined due to several factors, including the 2018 Lombok earthquake, insufficient budget allocation, and inadequate human resources. The study emphasizes the importance of addressing these challenges to enhance the office's performance in regional development. It is recommended that the office should improve its budget allocation and prioritize the recruitment of additional skilled human resources. The findings of this study provide valuable insights for policymakers and stakeholders in the public works and spatial planning sector to enhance the performance of the office and advance the development of the region.